2003
DOI: 10.1110/ps.0213603
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and biochemical characterization of LEAP‐2, a novel blood peptide expressed in the liver

Abstract: The human genome contains numerous genes whose protein products are unknown in terms of structure, interaction partner, expression, and function. To unravel the function of these orphan genes, it is of particular value to isolate native forms of protein and peptide products derived from these genes. From human blood ultrafiltrate, we characterized a novel gene-encoded, cysteine-rich, and cationic peptide that we termed liver-expressed antimicrobial peptide 2 (LEAP-2). We identified several circulating forms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
132
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(139 citation statements)
references
References 33 publications
3
132
1
Order By: Relevance
“…GAL1-10 Gallinacins (Gal-) 1-10, GAL1A Gal-1α, THP turkey heterophil peptide, TBD turkey β-defensin, BD07 MOUSE mouse β-defensin 7 (Q91V70) intestine, gall bladder and kidneys. These results are consistent with studies of human LEAP-2, which is also expressed in the liver, kidney and colon (Krause et al 2003). Chicken cathelicidin is expressed across a wide variety of tissues, but shows particularly high levels of expression in the bursa, testis and bone marrow, and is the only novel AMP to show expression in the gizzard.…”
Section: Resultssupporting
confidence: 89%
“…GAL1-10 Gallinacins (Gal-) 1-10, GAL1A Gal-1α, THP turkey heterophil peptide, TBD turkey β-defensin, BD07 MOUSE mouse β-defensin 7 (Q91V70) intestine, gall bladder and kidneys. These results are consistent with studies of human LEAP-2, which is also expressed in the liver, kidney and colon (Krause et al 2003). Chicken cathelicidin is expressed across a wide variety of tissues, but shows particularly high levels of expression in the bursa, testis and bone marrow, and is the only novel AMP to show expression in the gizzard.…”
Section: Resultssupporting
confidence: 89%
“…Shike et al (2002) showed that the LEAP-1 gene is expressed strongly in the liver but at lower levels in other tissues of bacterially challenged fish. With the recent discovery of LEAP-2 in mammals (Krause et al, 2003) and birds (Lynn et al, 2003), we have searched the fish EST databases to see if this molecule also exists in bony fish, especially salmonids. We found ESTs with high homology to LEAP-2 in rainbow trout, Atlantic salmon, winter flounder and zebrafish, although the latter was an incomplete sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Among the cysteine-rich peptides, defensins are the most well known molecules, containing three pairs of disulfidebridges. More recently LEAP (liver-expressed antimicrobial peptide) molecules with four and two pairs of disulfide bonds, named LEAP-1 and LEAP-2 respectively, have been isolated from human blood ultrafiltrate (Krause et al, 2000(Krause et al, , 2003 and the corresponding genes sequenced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPs disrupt the physical integrity of microbial membranes and also they function as a modulatory effector in the innate immunity of fish (Townes et al 2009;Li et al 2012). Liver-expressed antimicrobial peptide-2 (LEAP-2) is the second blood-derived antimicrobial peptide, which was first identified in human (Krause et al 2003). Similar with LEAP-1 (also termed hepcidin), LEAP-2 is cysteine-rich and predominantly expressed in the liver.…”
Section: Introductionmentioning
confidence: 99%